Effect of planting time on the incidence of papaya ringspot virus disease and yield of fruits - S.M. PRASAD, N. KUDADA and (Indian Phytopathology, 2002)
Field trials were conducted during 1994-96 to determine the effect of planting time on incidence of papaya ringspot virus (PRSV) disease in papaya [pawpaws] (cv. Farm Selection-1) and yield of fruits. Planting during October to December was effective in reducing natural incidence of PRSV and significantly greater fruit yields were recorded in the October planting than in the November and December plantings. Maximum fruit yield per plant was obtained from papaya transplanted during October. Stem girth, fruiting length (area on the stem on which fruits are borne) and circumference showed a positive and significant association with fruit yield per plant.